Lithium battery negative electrode material based on modified biomass carbon material and preparation method thereof

Through the combination of modified biomass carbon materials and nano-silicon, the structural damage and capacity decay caused by volume changes in the lithium-ion battery anode material during lithiation and delithiation are solved, and a lithium battery anode material with high energy density, circulation performance and stability is achieved.

CN119786569AActive Publication Date: 2025-04-08DONGGUAN YOUFANG NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411976819.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The volume of existing lithium-ion battery anode materials changes greatly during the lithiation and delithiation process, resulting in structural damage, capacity decay and rupture of the solid electrolyte interface layer, which cannot meet the global market's demand for high energy density, cycling performance and stability.

Method used

The modified biomass carbon material is combined with nanosilicon, and the dispersion and coating density of nanosilicon and conductive materials are improved through amination and sulfonation reactions to prepare a high-performance lithium battery negative electrode material.

Benefits of technology

It improves the first discharge capacity and normal temperature circulation performance of lithium batteries, improves the circulation performance at high and low temperatures, and enhances the stability and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220631040000101
    Figure BDA0005220631040000101
  • Figure BDA0005220631040000111
    Figure BDA0005220631040000111
Patent Text Reader

Abstract

The invention provides a lithium battery negative electrode material based on a modified biomass carbon material and a preparation method of the lithium battery negative electrode material. The preparation method comprises the following steps: (1) preparing modified nano silicon; (2) in a nitrogen atmosphere, carrying out ultrasonic dispersion on the modified nano silicon prepared in the step (1) and thionyl chloride, adding N, N-dimethylformamide, heating to 70-80 DEG C, adding a modified conductive material, and reacting at 70-80 DEG C for 20-25 hours to obtain a mixed solution; and (3) the mixed solution obtained in the step (2) is subjected to spray drying, the inlet temperature of spray drying is 220-250 DEG C, the outlet temperature is 120-150 DEG C, and the lithium battery negative electrode material based on the modified biomass carbon material is obtained. The prepared lithium battery negative electrode material is high in conductivity, the charging and discharging efficiency is improved, and meanwhile the service life of a lithium ion battery at different temperatures is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium battery negative electrode material based on modified biomass carbon material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries play a vital role in the electric vehicle (EV) industry. They are one of the core components of electric vehicles and provide the electricity required to drive the vehicle. Therefore, the development of advanced lithium-ion batteries with high energy density, high cycle performance, and high stability is essential to meet the growing demand for next-generation energy storage devices.

[0003] As a potential high-performance negative electrode material, silicon is regarded as one of the key candidates for the next generation of battery technology due to its high theoretical specific capacity. However, silicon faces several major challenges in practical applications: not only does it have a low ion diffusion rate and poor conductivity, but it also undergoes significant volume changes during lithiation and delithiation, which can lead to structural damage of the material, resulting in rapid decline in battery capacity. In addition, this volume change can also trigger the rupture of the solid electrolyte interface layer (SEI), further exacerbating capacity decay and reducing the rate performance of the battery.

[0004] In the prior art, some progress has been made in combining graphene with silicon materials to improve the electrochemical performance of silicon through various methods, but these solutions still have some shortcomings: the coating effect of graphene on silicon is not ideal, which is manifested in poor density and uniformity. Insufficient coating density will cause the electrolyte to directly contact with silicon, thereby forming a solid electrolyte interface layer (SEI), and the uneven coating may affect the rate performance of the battery.

[0005] At the same time, with the rapid development of my country's industry in the world, electric vehicle and electric vehicle manufacturers need to ensure the reliability and performance of batteries under different climatic conditions to meet the needs of the global market. Energy storage systems also need to operate stably in various environments, especially in remote areas or extreme climatic conditions. However, the negative electrode materials in existing technologies cannot meet the increasingly high demands of the global market.

[0006] Therefore, there is an urgent need for a lithium battery negative electrode material based on modified biomass carbon material and a preparation method thereof. Summary of the invention

[0007] The purpose of the present invention is to provide a lithium battery negative electrode material based on modified biomass carbon material and a preparation method thereof.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material, comprising the following steps:

[0010] (1) Preparation of modified nano-silicon:

[0011] S1: Mix nano-silicon and deionized water, and disperse them by ultrasonic at 5°C for 35 minutes to obtain a nano-silicon dispersion, wherein the concentration of the nano-silicon is 0.15-0.17 g / L;

[0012] S2: Add 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to the nano-silicon dispersion, stir evenly at 0-4°C to obtain a mixed solution, continue to add ethylenediamine to the mixed solution, react at 0-4°C for 15-17h, and fully wash the product with acetone / deionized water and dry it to obtain modified nano-silicon;

[0013] (2) Under a nitrogen atmosphere, ultrasonically disperse the modified nano-silicon prepared in step (1) and thionyl chloride, add N,N-dimethylformamide, raise the temperature to 70-80° C., add the modified conductive material, react at 70-80° C. for 20-25 hours, and obtain a mixed solution;

[0014] (3) spray drying the mixed solution of step (2), wherein the inlet temperature of the spray drying is 220-250° C. and the outlet temperature is 120-150° C., to obtain a lithium battery negative electrode material based on modified biomass carbon material.

[0015] Furthermore, the preparation method of the modified conductive material comprises the following steps:

[0016] (1) mixing carbon nanotubes, graphene and biomass carbon materials in a mass ratio of (0.3-0.5):1:(1.4-1.6) to obtain a mixture;

[0017] (2) 1 part by mass of fuming sulfuric acid and 95-100 parts by mass of water are mixed, stirred evenly, and then 30-35 parts by mass of the mixture are added, stirred at 80-85° C. for 3-5 hours, cooled to room temperature, filtered, and dried to obtain a modified conductive material.

[0018] The present invention improves the initial discharge capacity of the lithium battery by subjecting the nano silicon to amination and the conductive material to sulfonation. The modified nano silicon and the modified conductive material in the present invention react and are connected by covalent bonds, thereby improving the dispersibility between the nano silicon and the conductive material, improving the compactness and uniformity of the coating, thereby improving the initial discharge capacity of the lithium battery and improving the cycle performance at room temperature.

[0019] Furthermore, the preparation method of the biomass carbon material includes the following steps: taking 5 parts by mass of straw and crushing it to less than 40 mesh, mixing it evenly with 10-12 parts by mass of 1-allyl-3-methylimidazolium chloride, stirring it at 500-700 rpm for 15-17 hours, placing it in a tubular high-temperature furnace for sintering, heating it to 800-830°C at a heating rate of 3-5°C / min, maintaining the constant temperature for 2-3 hours, then cooling it to room temperature at a cooling rate of 3-5°C / min, grinding it into powder, and passing it through a 100-mesh sieve to obtain a biomass carbon material.

[0020] The present invention can improve the cycle performance of lithium batteries at high temperatures by using modified conductive fillers prepared by using carbon nanotubes, graphene and biomass carbon materials in specific ratios. Analysis shows that by adding carbon nanotubes, graphene and biomass carbon materials in specific ratios, a buffer space can be provided for nano-silicon, effectively alleviating its volume expansion during the charge and discharge process. This buffering effect can reduce the pulverization and shedding of electrode materials, maintain the structural integrity of the electrode, and thus improve the cycle stability of the battery.

[0021] Furthermore, the nano-silicon comprises nano-silicon I, nano-silicon II and nano-silicon III in a mass ratio of 1: (1.2-1.4): (0.5-0.7); the average particle size of nano-silicon I is 100nm, and the specific surface area is 60m 2 / g, model MG-Si-100; average particle size of nano-silicon II is 200nm, specific surface area is 45m 2 / g, model MG-Si-200; average particle size of nano-silicon III is 1000nm, specific surface area is 16m 2 / g, model MG-Si-1000.

[0022] The present invention can improve the first coulombic efficiency of lithium batteries by using nano silicon with specific parameters and ratios. Because the combination of nano silicon with different particle sizes and surface areas with carbon nanotubes, graphene and biomass carbon materials can produce a synergistic effect, by using nano silicon with different particle sizes, the pore structure and density of the electrode material can be optimized, a more compact electrode structure can be formed, the penetration of the electrolyte can be reduced, the formation and consumption of the SEI layer can be reduced, and the first coulombic efficiency of the lithium battery can be further improved.

[0023] Furthermore, the carbon nanotube has an inner diameter of 10-20 nm, a tube length of 5-15 μm, and a specific surface area of ​​120-180 m 2 / g of multi-walled carbon nanotubes.

[0024] Furthermore, the graphene has a thickness of 1-5 nm, a single-layer sheet diameter of 5-45 μm, an electrical conductivity of 100,000 S / m, and a specific surface area of ​​24 m 2 / g.

[0025] When the biomass carbon material prepared by the present invention is compounded with carbon nanotubes and graphene with specific parameters, the cycle performance of the negative electrode material of the lithium battery at low temperature can be improved. Under this condition, the synergistic effect of the biomass carbon material, carbon nanotubes and graphene builds a stable three-dimensional conductive network, which provides a channel for rapid transmission of lithium ions, reduces transmission resistance, and improves charging and discharging efficiency.

[0026] Furthermore, the mass ratio of the modified nano-silicon to the modified conductive material is (4-7):1.

[0027] Furthermore, the molar ratio of the dithionyl chloride to the modified nano-silicon is (1.5-2.0):1.

[0028] Furthermore, the molar ratio of N,N-dimethylformamide to thionyl chloride is (0.1-0.3):1.

[0029] Furthermore, the added amount of the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 20% to 23% of the mass of the nano-silicon; and the added amount of the N-hydroxysuccinimide is 20% to 23% of the mass of the nano-silicon.

[0030] Furthermore, the amount of ethylenediamine added is 3% to 6% of the volume of the mixed solution.

[0031] The present invention provides a lithium battery negative electrode material based on modified biomass carbon material prepared by the preparation method.

[0032] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0033] 1. The present invention improves the dispersion between the nano-silicon and the conductive material, improves the density and uniformity of the coating, thereby increasing the initial discharge capacity of the lithium battery and improving the cycle performance at room temperature.

[0034] 2. The modified conductive filler prepared by using a specific ratio of carbon nanotubes, graphene and biomass carbon materials can provide a buffer space for nano-silicon, effectively alleviating its volume expansion during the charge and discharge process. This buffering effect can reduce the pulverization and shedding of electrode materials, maintain the structural integrity of the electrode, and thus improve the cycle performance of lithium batteries at high temperatures.

[0035] 3. The present invention uses nano-silicon with specific parameters and ratios. The combination of nano-silicon with different particle sizes and surface areas with carbon nanotubes, graphene and biomass carbon materials can produce a synergistic effect. By using nano-silicon with different particle sizes, the pore structure and density of the electrode material can be optimized to form a denser electrode structure, reduce the penetration of the electrolyte, reduce the formation and consumption of the SEI layer, and improve the initial coulombic efficiency of the lithium battery.

[0036] 4. When the biomass carbon material prepared by the present invention is compounded with carbon nanotubes and graphene with specific parameters, the synergistic effect of the biomass carbon material, carbon nanotubes and graphene constructs a stable three-dimensional conductive network, which provides a channel for rapid transmission of lithium ions, reduces transmission resistance, improves charge and discharge efficiency, and can improve the cycle performance of lithium battery negative electrode materials at low temperatures. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The raw materials of the present invention are all commercially available and purchased from the following manufacturers:

[0039] 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, CAS: 25952-53-8.

[0040] Oleum, CAS: 8014-95-7, Guangdong Xiaoda Chemical Co., Ltd.

[0041] 1-Allyl-3-methylimidazolium chloride, Sigma-Aldrich, Product No. 43961.

[0042] Example 1

[0043] This embodiment provides a method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material, comprising the following steps:

[0044] (1) Preparation of modified nano-silicon:

[0045] S1: Mix nano-silicon and deionized water, and disperse them by ultrasonic at 5°C for 35 minutes to obtain a nano-silicon dispersion, wherein the concentration of the nano-silicon is 0.16 g / L;

[0046] S2: 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide were added to the nano-silicon dispersion, and stirred evenly at 4°C to obtain a mixed solution. Ethylenediamine was further added to the mixed solution, and the mixture was reacted at 4°C for 16 hours. The product was washed with acetone and deionized water in sequence, and dried to obtain modified nano-silicon;

[0047] The amount of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride added is 22% of the mass of nano silicon; the amount of N-hydroxysuccinimide added is 22% of the mass of nano silicon; and the amount of ethylenediamine added is 5% of the volume of the mixed solution.

[0048] Nano silicon includes nano silicon I, nano silicon II and nano silicon III with a mass ratio of 1:1.3:0.6; the average particle size of nano silicon I is 100nm and the specific surface area is 60m 2 / g, model MG-Si-100; average particle size of nano-silicon II is 200nm, specific surface area is 45m 2 / g, model MG-Si-200; average particle size of nano-silicon III is 1000nm, specific surface area is 16m 2 / g, model MG-Si-1000. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0049] (2) Under nitrogen atmosphere, the modified nano-silicon prepared in step (1) and thionyl chloride are ultrasonically dispersed, wherein the molar ratio of thionyl chloride to the modified nano-silicon is 1.7:1. N,N-dimethylformamide is added, wherein the molar ratio of N,N-dimethylformamide to thionyl chloride is 0.2:1; the temperature is raised to 75° C., and the modified conductive material is added, and the mixture is reacted at 75° C. for 22 hours to obtain a mixed solution; the mass ratio of the modified nano-silicon to the modified conductive material is 5:1.

[0050] (3) The mixed solution of step (2) is spray-dried, wherein the inlet temperature of the spray-drying is 230° C. and the outlet temperature is 130° C., to obtain a lithium battery negative electrode material based on modified biomass carbon material.

[0051] The preparation method of the modified conductive material comprises the following steps:

[0052] (1) mixing carbon nanotubes, graphene and biomass carbon materials in a mass ratio of 0.4:1:1.5 to obtain a mixture;

[0053] (2) 1 part by mass of fuming sulfuric acid and 98 parts by mass of water were mixed, stirred evenly, and then 32 parts by mass of the mixture were added, stirred at 82° C. for 4 h, cooled to room temperature, filtered, and dried to obtain a modified conductive material.

[0054] The preparation method of the biomass carbon material comprises the following steps: taking 5 parts by mass of straw and crushing it to less than 40 meshes, mixing it evenly with 11 parts by mass of 1-allyl-3-methylimidazole chloride, stirring it at 600 rpm for 16 hours, placing it in a tubular high-temperature furnace for sintering, heating it to 820°C at a heating rate of 4°C / min, maintaining the constant temperature for 2.5 hours, then cooling it to room temperature at a cooling rate of 4°C / min, grinding it into powder, passing it through a 100-mesh sieve, and obtaining the biomass carbon material.

[0055] The carbon nanotube has an inner diameter of 10-20 nm, a tube length of 5-15 μm, and a specific surface area of ​​120-180 m 2 / g multi-walled carbon nanotubes were purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0056] The graphene has a thickness of 1-5 nm, a single-layer sheet diameter of 5-45 μm, an electrical conductivity of 100,000 S / m, and a specific surface area of ​​24 m 2 / g. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0057] Example 2

[0058] This embodiment provides a method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material, comprising the following steps:

[0059] (1) Preparation of modified nano-silicon:

[0060] S1: Mix nano-silicon and deionized water, and disperse them by ultrasonic at 5° C. for 35 min to obtain a nano-silicon dispersion, wherein the concentration of the nano-silicon is 0.17 g / L;

[0061] S2: Add 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to the nano-silicon dispersion, stir evenly at 2°C to obtain a mixed solution, continue to add ethylenediamine to the mixed solution, react at 2°C for 17 hours, and fully wash the product with acetone / deionized water and dry it to obtain modified nano-silicon;

[0062] The amount of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride added is 20% to 23% of the mass of nano silicon; the amount of N-hydroxysuccinimide added is 23% of the mass of nano silicon; and the amount of ethylenediamine added is 6% of the volume of the mixed solution.

[0063] Nano silicon includes nano silicon I, nano silicon II and nano silicon III with a mass ratio of 1:1.2:0.7; the average particle size of nano silicon I is 100nm and the specific surface area is 60m 2 / g, model MG-Si-100; average particle size of nano-silicon II is 200nm, specific surface area is 45m 2 / g, model MG-Si-200; average particle size of nano-silicon III is 1000nm, specific surface area is 16m 2 / g, model MG-Si-1000. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0064] (2) Under nitrogen atmosphere, the modified nano-silicon prepared in step (1) and thionyl chloride are ultrasonically dispersed, wherein the molar ratio of thionyl chloride to the modified nano-silicon is 1.5:1. N,N-dimethylformamide is added, wherein the molar ratio of N,N-dimethylformamide to thionyl chloride is 0.3:1. The temperature is raised to 70° C., and the modified conductive material is added, and the mixture is reacted at 70° C. for 25 hours to obtain a mixed solution; the mass ratio of the modified nano-silicon to the modified conductive material is 7:1.

[0065] (3) The mixed solution of step (2) is spray-dried, wherein the inlet temperature of the spray-drying is 220° C. and the outlet temperature is 150° C., to obtain a lithium battery negative electrode material based on modified biomass carbon material.

[0066] The preparation method of the modified conductive material comprises the following steps:

[0067] (1) mixing carbon nanotubes, graphene and biomass carbon materials in a mass ratio of 0.3:1:1.4 to obtain a mixture;

[0068] (2) 1 part by mass of fuming sulfuric acid and 100 parts by mass of water were mixed, stirred evenly, and then 30 parts by mass of the mixture were added, stirred at 80° C. for 5 h, cooled to room temperature, filtered, and dried to obtain a modified conductive material.

[0069] The preparation method of the biomass carbon material comprises the following steps: taking 5 parts by mass of straw and crushing it into less than 40 meshes, mixing it evenly with 12 parts by mass of 1-allyl-3-methylimidazolium chloride, stirring it at 500 rpm for 17 hours, placing it in a tubular high-temperature furnace for sintering, heating it to 830°C at a heating rate of 3°C / min, maintaining the constant temperature for 2 hours, then cooling it to room temperature at a cooling rate of 5°C / min, grinding it into powder, passing it through a 100-mesh sieve, and obtaining the biomass carbon material.

[0070] The carbon nanotube has an inner diameter of 10-20 nm, a tube length of 5-15 μm, and a specific surface area of ​​120-180 m 2 / g multi-walled carbon nanotubes were purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0071] The graphene has a thickness of 1-5 nm, a single-layer sheet diameter of 5-45 μm, an electrical conductivity of 100,000 S / m, and a specific surface area of ​​24 m 2 / g. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0072] Comparative Example 1

[0073] The difference between this comparative example and Example 1 is that carbon nanotubes, graphene and biomass carbon material are mixed in a mass ratio of 1:1:1 to obtain a mixture.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 1 is that the modified conductive material is replaced by graphene, the graphene thickness is 1-5nm; the single layer diameter is 5-45μm, the conductivity is 100000S / m, and the specific surface area is 24m 2 / g. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0076] Comparative Example 3

[0077] The difference between this comparative example and Example 1 is that the nano-silicon comprises nano-silicon I, nano-silicon II and nano-silicon III in a mass ratio of 1:1:1; the average particle size of nano-silicon I is 100nm, and the specific surface area is 60m 2 / g, model MG-Si-100; average particle size of nano-silicon II is 200nm, specific surface area is 45m 2 / g, model MG-Si-200; average particle size of nano-silicon III is 1000nm, specific surface area is 16m 2 / g, model MG-Si-1000. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0078] Comparative Example 4

[0079] The difference between this comparative example and Example 1 is that the carbon nanotubes have an inner diameter of 15-30 nm, a tube length of 10-30 μm, a conductivity of 1000 S / m, and a specific surface area of ​​50-80 m 2 / g multi-walled carbon nanotubes were purchased from Xianfeng Nano.

[0080] Comparative Example 5

[0081] The difference between this comparative example and Example 1 is that the number of carbon atom layers of the graphene is 4-6; the diameter of the single layer is 200nm, and the specific surface area is 200m 2 / g. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd. Model MG-GR-01.

[0082] Performance Testing

[0083] The negative electrode materials and conductive carbon black prepared in Examples 1-2 and Comparative Examples 1-5 were ground in a mortar to mix them evenly, added to a PVDF N-methylpyrrolidone (NMP) solution, stirred evenly, and a slurry was prepared, wherein the mass ratio of negative electrode material: conductive carbon black: PVDF was 90:5:5, and coated on a copper foil, dried, and rolled to form a negative electrode sheet. A metal lithium sheet was used as a counter electrode, Celgard2400 was used as a diaphragm, and 1 mol / LLiPF6 / EC (ethylene carbonate) + DMC (dimethyl carbonate) + EMC (ethyl methyl carbonate) (volume ratio 1:1:1) was used as an electrolyte. A simulated battery was assembled in an argon-filled glove box, and after standing for 12 hours, the first charge specific capacity and the first coulomb efficiency were measured.

[0084] In the charge and discharge voltage range of 2.5-4.2V, the cycle test performance was tested at different temperatures (-30℃, 25℃, 50℃) and a charge and discharge rate of 1.0C / 1.0C.

[0085] Table 1 Performance test results

[0086]

[0087]

[0088] From the above performance test results, it can be seen that the batteries prepared with the negative electrode materials of Examples 1-2 have excellent comprehensive performance, especially the cycle performance under high and low temperatures is improved. The comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the raw materials.

[0089] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the ratios of carbon nanotubes, graphene and biomass carbon materials are different, and the cycle performance at high temperature decreases; in comparative example 2, the modified conductive material is replaced with graphene, and the battery performance decreases to varying degrees; in comparative example 3, the ratio of nano-silicon is different, and the first coulomb efficiency of the lithium battery decreases; in comparative example 4, the carbon nanotube parameters are different, and in comparative example 5, the graphene parameters are different, and the battery cycle performance at low temperature decreases. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0090] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material, characterized in that: The following steps are involved: (1) Preparation of modified nano-silicon: S1: mixing nano-silicon and deionized water, and dispersing by ultrasonication to obtain a nano-silicon dispersion, wherein the concentration of the nano-silicon is 0.15-0.17 g / L; S2: adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to the nano-silicon dispersion, stirring evenly at 0-4°C to obtain a mixed solution, adding ethylenediamine to the mixed solution, reacting at 0-4°C for 15-17h, washing, and drying to obtain modified nano-silicon; (2) Under a nitrogen atmosphere, ultrasonically disperse the modified nano-silicon prepared in step (1) and thionyl chloride, add N,N-dimethylformamide, raise the temperature to 70-80° C., add the modified conductive material, react at 70-80° C. for 20-25 hours, and obtain a mixed solution; (3) spray drying the mixed solution in step (2) to obtain a lithium battery negative electrode material based on modified biomass carbon material.

2. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 1, characterized in that: The preparation method of the modified conductive material comprises the following steps: (1) mixing carbon nanotubes, graphene and biomass carbon materials in a mass ratio of (0.3-0.5):1:(1.4-1.6) to obtain a mixture; (2) 1 part by mass of fuming sulfuric acid and 95-100 parts by mass of water are mixed, stirred evenly, and then 30-35 parts by mass of the mixture are added, stirred at 80-85° C. for 3-5 hours, cooled to room temperature, filtered, and dried to obtain a modified conductive material.

3. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 2, characterized in that: The preparation method of the biomass carbon material comprises the following steps: taking 5 parts by mass of straw, crushing it, and evenly mixing it with 10-12 parts by mass of 1-allyl-3-methylimidazolium chloride, stirring it for 15-17 hours, placing it in a tubular high-temperature furnace for sintering, heating it to 800-830° C., maintaining the constant temperature for 2-3 hours, cooling it to room temperature, grinding it, and sieving it to obtain the biomass carbon material.

4. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 1, characterized in that: Nano silicon includes nano silicon I, nano silicon II and nano silicon III in a mass ratio of 1: (1.2-1.4): (0.5-0.7); the average particle size of nano silicon I is 100nm, and the specific surface area is 60m 2 / g; the average particle size of nano-silicon II is 200nm, and the specific surface area is 45m 2 / g; the average particle size of nano-silicon III is 1000nm, and the specific surface area is 16m 2 / g.

5. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 2, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes, with an inner diameter of 10-20 nm, a tube length of 5-15 μm, and a specific surface area of ​​120-180 m 2 / g.

6. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 2, characterized in that: The graphene has a thickness of 1-5 nm, a single-layer sheet diameter of 5-45 μm, an electrical conductivity of 100,000 S / m, and a specific surface area of ​​24 m 2 / g.

7. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 1, characterized in that: The mass ratio of the modified nano-silicon to the modified conductive material is (4-7):

1.

8. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 1, characterized in that: The molar ratio of the thionyl chloride to the modified nano silicon is (1.5-2.0):1; the molar ratio of the N,N-dimethylformamide to the thionyl chloride is (0.1-0.3):

1.

9. The method for preparing a negative electrode material for a lithium battery based on modified biomass carbon material according to claim 1, characterized in that: The added amount of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 20% to 23% of the mass of nano silicon; the added amount of N-hydroxysuccinimide is 20% to 23% of the mass of nano silicon; and the added amount of ethylenediamine is 3% to 6% of the volume of the mixed solution.

10. A negative electrode material for a lithium battery based on a modified biomass carbon material obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nano silicon-carbon composite material for negative electrode of lithium battery and preparation method thereof

    CN106920951A

  • Silicon-carbon negative pole material for lithium ion battery and preparation method thereof

    CN108630912A

  • Graphene modified silicon negative electrode material and preparation method and application thereof

    CN114613955A

  • Method for preparing negative electrode of lithium ion battery and lithium ion battery

    US20180241030A1